Errant polychaetes of the continental plattaform of Tamaulipas, México. - Delgado-Blas, V. Hugo (2000)
24 species of errant polychaetes have been recorded for the eastern Mexican continental shelf: Two Phyllodocidae, one Pilargidae, two Syllicdae, four Nereididae, two Glyceridae, two Goniadidae, three Nephtyidae, two Onuphidae, five Lumbrineridae y one Dorvilleidae. Two of these were the first to be recorded in Mexico, two from Mexican waters in the Gulf of Mexico and 11 new ones recorded in Tamaulipas.